2018
DOI: 10.1007/s00347-018-0723-z
|View full text |Cite
|
Sign up to set email alerts
|

Pilotstudie zur Erfassung von Schlafstörungen bei Erblindung oder relevanter Sehbeeinträchtigung

Abstract: The non-24-hour sleep-wake disorder is a frequent problem among people with no light perception, associated with problems falling asleep, maintaining sleep, and daytime sleepiness. The perception of light as an external cue for our circadian rhythm plays a key role. However, sleep disruption is not fully explained by non-24, making a detailed sleep history essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…In the present survey, half respondents suffered from sleep disorders (falling asleep, sleep maintenance, and daytime sleepiness), more likely those affected by visual disabilities. Sleep disorders significantly increased during lock-down [23], particularly among people with visual impairments, probably for a reduced perception of light, which plays a fundamental role in the circadian rhythm [24]. Recent studies reported that the prevalence of insomnia and hypersomnia is around 40% and continuously increasing among individuals fearing SARS-CoV-2 contagion and social isolation [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the present survey, half respondents suffered from sleep disorders (falling asleep, sleep maintenance, and daytime sleepiness), more likely those affected by visual disabilities. Sleep disorders significantly increased during lock-down [23], particularly among people with visual impairments, probably for a reduced perception of light, which plays a fundamental role in the circadian rhythm [24]. Recent studies reported that the prevalence of insomnia and hypersomnia is around 40% and continuously increasing among individuals fearing SARS-CoV-2 contagion and social isolation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Aus Studien, welche nur für die USA durchgeführt worden sind, geht weiterhin hervor, dass schätzungsweise 50 %-70 % der blinden Menschen an einer Non-24 leidet [12]. Erste epidemiologische Daten zur Häufigkeit der Non-24 für Deutschland ergaben, dass in einem Kollektiv von 111 blinden und sehbehinderten Menschen 72,2 % der blinden Probanden nach WHO-Stufe 5 (26/36) und 21,3 % der sehbehinderten Probanden nach WHO Stufe 1-4 (16/75) Hinweise für das Vorliegen einer Non-24 zeigten [13].…”
Section: Definitionunclassified